Combination of Medicinal Herbs KIOM-79 Reduces Advanced Glycation End Product Accumulation and the Expression of Inflammatory Factors in the Aorta of Zucker Diabetic Fatty Rats. (15th February 2011) - Sohn, Eunjin; Kim, Junghyun; Jeong, Il Ha; Kim, Chan Sik; Kim, Young Sook; Kim, Jin Sook
Abstract : Previous studies have reported that KIOM-79 shows a strong inhibitory effect on AGE formation and inhibited a proinflammatory state in a murine macrophage cell line. In the present study, we investigated the effect of KIOM-79 on AGE accumulation and vascular inflammation in the aorta of Zucker diabetic fatty (ZDF) rats, a commonly used model of type 2 diabetes. Seven-week-old male ZDF rats were treated with KIOM-79 (50 mg/kg) once a day orally for 13 weeks. We examined the dissected aortas for AGE accumulation, expression of the receptor for AGEs (RAGE), and the expression of proinflammatory factors, including monocyte chemoattractant protein-1 (MCP-1), vascular endothelial growth factor (VEGF), and vascular adhesion molecule-1 (VCAM-1). Nuclear factor-kappaB (NF-κB) and inducible nitric oxide synthase (iNOS) were also measured by Southwestern histochemistry, electrophoretic mobility shift assay (EMSA), and immunohistochemistry, respectively. KIOM-79 markedly reduced the accumulation of AGEs and the expression of RAGE in the aorta. We also found that KIOM-79 attenuated the expression of inflammatory factors including NF-κB, MCP-1, VEGF, VCAM-1, and iNOS in the aortas of ZDF rats. These data suggest that KIOM-79 may prevent or retard the development of inflammation in diabetic vascular disease.